A study on the effectiveness of union in F&N Beverages Manufacturing Sdn Bhd and F&N Beverages Marketing Sdn Bhd / Ashura Shuhada Azizan - Azizan, Ashura Shuhada (Faculty of Business and Management, 2014)
Since the perceived efficiency of union’s is one of the best predictors of an individual’s willingness to vote for or join union, or maybe to know whether the role of union are effective enough or not. Employees might join union because they expected that union will represent for them to the management if any problems or issues occur. Sometimes they ask, does the union established are effective in handling their members’ problem or meet their member’s expectation, or does the union leader play their exactly important role towards their union members. And some of the employees also refuse to join union because they might afraid of having problems with management. This study conducted to measure what is the element to ensure the effectiveness of the union. Data were gathered through a survey of 90 union members of three active unions in F&N Beverages Manufacturing Sdn Bhd and F&N Beverages Marketing Sdn Bhd in Shah Alam, Malaysia.